Perspectives on Global University Networks - Middlehurst, Robin (International Higher Education, 2015)
Global networks are proliferating and diversifying between higher education providers and other sectors and groups. Some authors suggest this represents a process of de-nationalization, others that approaches to internationalization that de-nationalize the university will fail. Looking to the past, establishing international consortia and networks appears to have been a response to a range of major structural challenges affecting higher education. Some of these resonate today, but there are also new competitive challenges that encourage institutions to join networks or align themselves with partners for competitive advantage, for substantive and reputational gains. The consortia and networks that exist today illustrate both diversity and coalescence around multiple themes. These include functional and activity-based themes as well as shared interests and values. The question of sustainability over time remains as some networks have survived decades while others have disappeared. Those that recognise cultural, political and intellectual differences and the need to achieve mutual benefits are more likely to be sustainable.